The nature of hilot a case study on the views and perceptions on "hilot" as a way of "pagpunit" among residents of Dulag, Leyte - Kempis, Grace A. (1998)
The focus of this research paper is on the nature and effectivity of "hilot" in "pagpunit". The respondents were 3 "parahilot" and 3 "nagpahilot" who were interviewed by the researcher on a face to face interaction using a prepared questionnaire and tape recorder. "Hilot" was viewed by the "nagpahilot" as the last alternative for reducing the family size although it poses greater risks to their life. Also, its effectivity can be traced on the number of times they turned to "hilot" with its underlying reason of financial crisis experienced in their family and to lessen family size and spacing. On the other hand, the "parahilot" perceived the "hilot" as a personal responsibility to help pregnant women by performing the "punit". An apparent explanation to these may be the lower socio-economic status of the "nagpahilot" while self involvement on the side of the "parahilot". Moreover, "hilot" is not a source of living for all the "parahilot", for the payment goes to offerings.